Pencak Silat Front Kick Speed Reviewed From Leg Length and Leg Power (Correlation Study on Pencak Silat Extracurricular Students MTs Sudirman Jatiyoso) - Bibit Waluyo; Eko Sudarmanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of the research is to find out how big  the speed of the front  kick of  martial arts is reviewed from the length of the legs and the power of the legs of the  Pencak Silat extracurricular students at MTs Sudirman Jatiyoso. The population of this study was 20 extracurricular students of pencak silat MTs Sudirman Jatiyoso. Sampling in this study used the total sampling method, which is to take a sample as a whole, with condition 1). Attendance above 80% and 2) Included in the two teams that have participated in the match, so that 20  MTs Sudirman Jatiyoso were obtained as research samples. The variables of this study are Limb Muscle Power and Speed. The data collection method uses the sports measurement test method. The data were analyzed using descriptive statistics and the computerized system of the SPSS 16.00 program. The results of data processing and analysis, the author concludes that: 1). From the results of the analysis of Pearson correlation calculation data between limb power and front kick results  in extracurricular martial arts painters obtained the value r count (ro) = 0. 082 (P ˂ 0.05), Then H0 is rejected and H1 is accepted means that there is a significant relationship between Limb Power and Front Kick results  in Extracurricular martial arts painters. 2). From the results of Pearson's correlation calculation analysis between Kecepatan and Front Kick  in martial arts extracurriculars, the value r count (ro) = 0 was obtained. 913 (P <0.05), Then H0 is rejected and H1 is accepted means that there is a significant relationship between Speed and Front Kick in  martial arts Extracurriculars in MTs Sudirman Jatiyoso. 3). From the results of the analysis of Power Limb  and Speed data  obtained 0.890 (P < 0.05), it means that there is a significant relationship between Power Limbs and Speed to Front Kicks in martial arts extracurriculars at MTs Sudirman Jatiyoso.